The Value of Cooperation in the Farming Activities of the Nagekeo Community: Its Implementation in Classroom Instruction - Ani, Yuventa Hendrika; Fonga, Thresia Arnoldine; Neur, Maria Yolanda; Nago Azi, Maria Dominika; Sode, Anastasia; Dadi, Maria Yosefina; Kasi, Yohanes Freadyanus (Pedagonal : Jurnal Ilmiah Pendidikan, 2024)
The value of cooperation in the farming activities of the Nagekeo district residents has been preserved since ancient times. There are many values contained in farming activities which are used as local guidelines. The aim of this research is to depict the value of cooperation in farming activities in the Mbay II sub-district, Nagekeo Regency, which can be related to classroom instruction. The research uses descriptive qualitative methods to explore the cultivation of cooperation value in farming activities in depth. The data were collected using interview and then analysed using qualitative descriptive analysis with interview guide instruments. The participants in this research consist of the members of Karya Nyata 6 farmer group in Mbay II Village, Nagekeo Regency, East Nusa Tenggara. The results of this research show that in farming activities there are cooperation values such as; (1) togetherness, (2) solidarity, (3) discipline and (4) responsibility which can be related to classroom instructions. Farming activity that instils the value of cooperation is a good value in social life. So, the value of working together in farming activities can be continued by students if it is brought into classroom instructions.